Distributed average tracking for uncertain directed multiagent networks. Issue 4 (March 2023) - Wu, Jiaxin; Xiang, Linying; Wang, Wuguang
Abstract: This paper studies a distributed average tracking problem of uncertain multiagent systems over directed graphs. The basic idea is to establish an appropriate reference model by introducing an adaptive control scheme. The output of the reference model is the average of multiple time-varying reference signals. This implies that the reference model partially solves the problem of distributed average tracking of directed graphs. Moreover, an appropriate control law is designed to make the output of the multiagent system with uncertain parameters approaches the average of the reference signals from the reference model. The feasibility of the proposed scheme is theoretically proved and the effectiveness of the scheme is verified through a simulation example.